ALIRAN BASRAH; SEJARAH LAHIR, TOKOH DAN KARAKTERISTIKNYA - Rahmap Rahmap (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2014)
Since Basra was a trading port for Iraq in the Arab Gulf, foreign influences that affected the progress in the field of trade and investment. Here in this port, encounters occurred between Arabs, Persians and Indians as well as between the religions of Christianity, Judaism, Majus and Islam. The closeness between Basra and the Gandisabur school in Persia that studied the Persian, Greek, and Indian culture has generated a mix of culture as a whole. During the period of Umar ibn Abdul Aziz, translation works on medical books were carried out by Masir Haubah. The same thing was also undertaken by Abdullah al-Muqaffa’ who was fluent in Arabic and Persian. He translated books on the Persian literature and history into Arabic. From the son of Abdullah al-Muqaffa, Muhammad, the Arabic translation of Aristotle’s science of logic Kalilah wa Dimnah was produced. There was also a Jewish translator named Hunain Ibn Ishaq, who translated books and got rewards in the form of gold for each weight of books he translated. In Basra, there was a school of Mu'tazilah that learnt the Greek sciences. This strongly affected the school of sciences he learnt such as the science of kalam and nahwu in terms of taqsim, ta’lil, ta’wil dan qiyas.